Влияние стиля руководства командира подразделения на формирование индивидуальных и коллективных ментальных моделей взаимодействия военнослужащих в ходе выполнении служебно-боевых задач - Mikhail I. Fedorishin (Vestnik Yaroslavskogo gosudarstvennogo universiteta im. P. G. Demidova. Seriya gumanitarnye nauki, 2026)
The article presents the results of an empirical study on the influence of a unit commander’s leadership style on the formation of integral indicators of individual mental models (commonality, accuracy, effectiveness) and parameters of collective mental models of interaction among military personnel (cohesion, role performance effectiveness, team member activity, overall mental model effectiveness) in the National Guard troops. The study involved 378 third-year cadets from military institutes. Using one-way analysis of variance (ANOVA) and Fisher’s LSD post-hoc test, statistically significant differences were established in all studied parameters depending on the commander’s leadership style. It was found that democratic and authoritarian leadership styles contribute to the formation of higher indicators of commonality, accuracy, and effectiveness of individual mental models. The democratic leadership style determines the greatest expression of cohesion, favorable atmosphere, and effectiveness of the collective mental model of interaction among military personnel. The laissez-faire leadership style, while demonstrating the lowest indicators on individual mental model parameters, provides statistically significantly higher values on the parameter of role performance effectiveness compared to other styles. The interpretation of the obtained results is carried out within the framework of the metasystem approach to the analysis of managerial activity and collective interaction.